(untitled) - Shaw, Colin (New York, N.Y., 2005)
In his previous groundbreaking book with John Ivens, Colin Shaw looked at the development of the conceptual framework for the customer experience together with examples of best practice and strategies for implementation. As predicted the customer experience has become the next competitive battleground. The current book will explore the subject in more depth with new research and best practice and show companies and organizations how to identify where they are and how to revolutionize their customer experience.
Keywords: Customer services,Consumer satisfaction,Experience,Customer relations